PERANCANGAN SISTEM TRANSMISI MESIN PENIRIN MINYAK UNTUK MENINGKATKAN KUALITAS KRUPUK - Akhyat Nur Ashariyanto; Pongky Lubas Wahyudi; Wisnu Yulianto Nugroho; Dian Setiya Widodo (Jurnal Inovasi Teknologi Manufaktur, Energi dan Otomotif, 2023)
In general, today's small industries, there are still many cracker entrepreneurs who use the manual method, that is, they still need human power as a source of propulsion, as well as when draining oil is still done manually. As is the case with the object of this study, namely the colorful cracker business in Rungkut, where the oil drainer for cracker production still uses the conventional method, namely draining it for a while naturally by placing it in a container made of strimin wire. This is what causes the draining of the oil on the crackers to be not optimal, where the oil should be used 2 to 3 times for frying, but what happens is not optimal and a lot is wasted. As well as the quality of the crackers that are not optimal, for example, the crackers go rancid quickly and the draining process is relatively long. Oil Drainer Machine is a machine that works by rotating force on the filter tube which results in residual oil found on the surface of the crackers which after frying separate from the crackers. In fulfilling the working mechanism of the oil slicer machine transmission system, the design method designed is the shaft, pulley, and v-belt sections in order to produce optimal and efficient productivity. From the design results, the results obtained from the calculation of the shaft diameter are 8.15mm and the diameter used is 25mm. The results of this machine pulley calculation use pulleys with a size of 4 inches on the motor shaft and 8 inches on the drive shaft and the circumference of the v-belt is 1,108.62mm. The results of the test resulted in a more optimal filtering as desired, a fast draining process, the crackers were not broken, and the results of the crackers were more evenly distributed.